An Empirical study on Massive Open Online Courses(MOOCs) - Shidaganti, Ganeshayya; Loukham, Alex; Prakash S, Prakash S (International Journal of Computer Sciences and Engineering, 2025)
The term Massive Open Online Courses (MOOCs) have drawn a lot of attention from various institutions across the world. There is an immense amount of idealism and altruism in the words of drivers who are making the MOOC movement. It is perhaps the most versatile form of educating interested learners because of its openness and availability. Over the recent years, it has brought upon a very innovative way of learning and made Technology Enhanced Learning (TEL) effective. An encouragement has been brought upon the elite universities in setting up learning platforms like the edX, Coursera, Udactity and various others. In other words, the data being collected through this learning platform can be used to retrieve useful information and henceforth be used to help students on having improvements academically. It is therefore crucial for modern learners to understand the concept of MOOCs. This empirical study has been carried out to give insights about what MOOCs actually is. The history, the motivation behind the development of this style of education, the different forms of MOOCs and some of the major challenges which the designers are still struggling to overcome have been identified and discussed in this paper.